Engenharia simultânea na produção de edifícios de múltiplos pavimentos: cenário potencial na região metropolitana de Curitiba - Silva, Odila Rosa Carneiro da (2013)
With the revolution of the construction industry in Brazil, it becomes necessary to promote its improvement and renovation. This sector in its current state has a segmentation between the stages of a project and its execution, whose conformation creats a barrier between phases that are necessarily independent. This discontinuity, added to failure in organization of informations, hampers the data recovery, and makes management, designers and project professionals to take decisions based on their intuition and experience. This thesis aims to evaluate the process of the exchange of information and collaboration among professionals in the production cycle in building construction, apropriating the grounds and criteria proposed by Concurrent Engineering. This concept has as its principle to promote the development of parallelization of activities in the product development, as well as the feedback of information and data genereted during its course. For this reason it has served as hypothesis to unify the project and its execution, it aims to ensure that decisions are validated by diferent profissionals and stages before its efective implementation. It was used as methodology the following research tools: literature review, field research and a questionary, focused to professionals in construction industry. This strategy of research has provided the identification of weak points in the process (in desagreement with the principles of Concurrent Engineering), rasing of issues to be incorporated into the collective conscious of the process through a systemic approach of activities, and the subsequent proposal of improvement criterion for their actions. As a result of this research, it was proposed improvement actions and also the improvement of activities that has already presented ambased on Concurrent Engineering criterion, underdeveloped, however. These propositions discuss the process of production in construction industry in its totality, through efective communication among professionals, sequence of activities, collaboration between functions and mainly the simultaneity of actions.